Ukrainian communication and media in Romania: from birth and progress to regress - Bidzilya, Yuriy M.; Haladzhun, Zoriana V.; Georgiievska, Viktoriia V.; Solomin, Yevhen O.; Sydorenko, Nataliia M. (Linguistics and Culture Review, 2021)
Due to the complex geopolitical processes of the twentieth century, Ukrainians became part of various states, in particular, part of this ethnic group became part of Romania. Taking into consideration the historical-political and social conditions, the authors of the paper give complex analysis of the peculiarities of the ethnocultural communication of the Ukrainians of Romania, the establishment and development of the Ukrainian-language press in this country, examines the main problems of the modern functions of the Ukrainian printed mass media and outlines the possible perspectives of their development. The Ukrainian language went through changes in education and mass media in Romania. The situation of the Ukrainian mass media worsened in Romania during the interwar period (especially in the 1930s) due to assimilation processes and turning Ukrainians into Romanians. The expansion of the Ukrainian information communication segment in Romania began with the introduction of the native-language primary and second education (7 grades) in 1948. The Ukrainian printed mass media of Romania are too weak today, they are published irregularly, have too weak influence on the cultural life of the Ukrainian group in this country.